Pengaruh Panjang Tabung dan Radius Fillet Terhadap Faktor Keamanan Tabung Motor Roket Dextrose Menggunakan Ansys Workbench - Lasinta Ari Nendra Wibawa; Unggul Satrio Yudhotomo; Yudi Haryanto; Rahadyan Lingga Laksita (P3M Politeknik Negeri Cilacap, 2021)
The rocket motor tube is the main component of the Dextrose rocket. This paper aims to investigate the effect of tube length and fillet radius on the safety factor of a dextrose rocket motor tube using Ansys Workbench. The Dextrose rocket tube uses Al 6063-T5 material with an outer diameter of 32 mm, a wall thickness of 3 mm, and internal pressure of 5 MPa. The rocket motor tube length is varied by 200, 250, 300, and 350 mm. The fillet radius uses variations of 3, 4, and 5 mm. The analysis was carried out using the finite element method with the help of Ansys Workbench. The simulation results show that the safety factor does not have a significant effect on changes in the length of the rocket tube. The safety factor increases as the fillet radius increases.